2. Work in Progress: Anchoring Roman rule: Rome-oriented festivals in the Greek world - Vliet, Robin van (Teiresias Journal Online, 2022)
Anchoring Roman rule: Rome-oriented festivals in the Greek world (supervisors Prof. Dr. Onno van Nijf and Dr. Christina Williamson). Date range: April 2019 – March 2024.